PERILAKU HIDUP BERSIH DAN SEHAT (PHBS) ANAK DI PANTI ASUHAN AL-AKBAR PEKANBARU - Meigy Adella Putri; Yoserizal " (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2017)
Clean and healthy life behaviors (PHBS) is one of the behaviors that are relatedto the person’s activities or efforts to improve health based on consciousness, sothat it is able to prevent disease as well as play an active role in realizing ahealthy environment by way of regular exercise, not to smoke, enough rest, and apositive lifestyle. The orphanage is a container that accommodate orphans. Whereorphans (or children who deposited by their parents who can not afford) usuallystay, get an education, and also provided a wide range of skills in order to beuseful in their life later. Al-Akbar orphanage is an orphanage that built toaccommodate orphans, orphaned, strays, needy children and abandoned children.The orphanage Al-Akbar is located at Jalan Soekarno Hatta, Arengka Atas,Pekanbaru City. The orphanage Al-Akbar was founded in 2009 and up to now thefoster child in orphanage Al-Akbar Pekanbaru amounts to 40 children. Thepurpose of this research is to know the implementation of the PHBS in theorphanage Al-Akbar Pekanbaru as well as knowing the driving and inhibitingfactors in implementation of the PHBS in the orphanage Al-Akbar Pekanbaru.This research uses descriptive quantitative research methods. From the results ofresearch conducted, the implementation of the PHBS in the orphanage Al-AkbarPekanbaru is included in the medium category, because of the eight indicatorsabout the behavior of clean and healthy life there are some indicators that cannotbe carried out properly. The driving factors of the implementation of the PHBS inthe orphanage Al-Akbar Pekanbaru that is 8 indicators behavior of clean andhealthy lifestyles in school age children that can be applied to children inorphanage Al-Akbar Pekanbaru, as well as the level of knowledge the children inorphanage Al-Akbar Pekanbaru that shows good category. Inhibiting factors ofthe implementation of the PHBS in the orphanage Al-Akbar Pekanbaru that is thelack of infrastructure in the orphanage Al-Akbar Pekanbaru as means ofsupporting the implementation of the PHBS in the orphanage Al-AkbarPekanbaru.Keyword : PHBS, Orphanage